Protective Application of Morus and Its Extracts in Animal Production - Lixue Wang; Huaqi Gao; Cui Sun; Lingxia Huang (Animals, 2022)
Different components of the mulberry tree (fruits, leaves, twigs, and roots) are rich in active compounds, and have been reported to possess potent beneficial properties, including antioxidative, anti-inflammatory, antimicrobial, anticancer, anti-allergenic, antihypertensive, and neuroprotective. The mulberry and its extracts can effectively improve the growth performance and fitness of animals. They not only possess the properties of being safe and purely natural, but also they are not prone to drug resistance. According to the literature, the supplemental level of the mulberry and its extracts in animal diets varies with different species, physiological status, age, and the purpose of the addition. It has been observed that the mulberry and its extracts enhanced the growth performance, the quality of animal products (meat, egg, and milk), the antioxidant and the anti-inflammatory responses of animals. Furthermore, the mulberry and its extracts have antibacterial properties and can effectively moderate the relative abundance of the microbial populations in the rumen and intestines, thus improving the immunity function of animals and reducing the enteric methane (CH4) production in ruminants. Furthermore, the mulberry and its extracts have the potential to depurate tissues of heavy metals. Collectively, this review summarizes the nutrients, active compounds, and biological functions of mulberry tree products, as well as the application in livestock production with an aim to provide a reference for the utilization of the mulberry and its extracts in animal production.